2022
DOI: 10.1088/1755-1315/1114/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Risk Assessment and Spatial Distribution of Heavy Metals of Agricultural Soils in Nganjuk Regency, Indonesia

Abstract: This research measures the lead, cadmium, copper, nickel, chromium, and arsenic in the paddy fields in Nganjuk Regency. Moreover, this research identifies the effect of these metals to the environment and their location. 105 topsoil samples were collected. The AAS was utilized to ascertain the elemental composition of the soil samples. Numerous soil pollution and ecological risk indices, such as Igeo, PI, IPI, PLI, and PERI, were used to analyze the situation. Spline interpolation with ArcGIS 10.2 was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is found that the contents of Ba, Cr, Fe, Hg, Mn and Zn (mg kg− 1) in caviar samples were 0.95, 0.27, 71.3, 1.44, 0.01 and 17.0, respectively. Based on this results, monitoring of chemicals accumulation in the foodstuff is recommended since the concentration of Fe and Hg were higher than Maximum Permissible Limits in the caviar samples [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the contents of Ba, Cr, Fe, Hg, Mn and Zn (mg kg− 1) in caviar samples were 0.95, 0.27, 71.3, 1.44, 0.01 and 17.0, respectively. Based on this results, monitoring of chemicals accumulation in the foodstuff is recommended since the concentration of Fe and Hg were higher than Maximum Permissible Limits in the caviar samples [ 14 ].…”
Section: Introductionmentioning
confidence: 99%